AngiomiRs—Key Regulators of Angiogenesis - Wang, Shusheng (2009)
The formation of new blood vessels through the process of angiogenesis is critical in vascular development and homeostasis. Aberrant angiogenesis leads to a variety of diseases, such as ischemia and cancer. Recent studies have revealed important roles for miRNAs in regulating endothelial cell (EC) function, especially angiogenesis. Mice with EC-specific deletion of Dicer, a key enzyme for generating miRNAs, display defective postnatal angiogenesis. Specific miRNAs (angiomiRs) have recently been shown to regulate angiogenesis in vivo. miRNA-126, an EC-restricted miRNA, regulates vascular integrity and developmental angiogenesis. miR-378, miR-296, and the miR-17~92 cluster, contribute to tumor angiogenesis. Manipulating angiomiRs in the settings of pathological vascularization represents a new therapeutic approach.